2019
DOI: 10.1136/openhrt-2019-001161
|View full text |Cite
|
Sign up to set email alerts
|

Long QT syndrome is associated with an increased burden of diabetes, psychiatric and neurological comorbidities: a nationwide cohort study

Abstract: ObjectiveStudies have suggested a shared genetic aetiology between congenital long QT syndrome (LQTS) and diabetes, epilepsy and mental disorders. We investigated the prevalence of metabolic, neurological and psychiatric comorbidities in LQTS patients.MethodsThis retrospective cohort study was based on data from nationwide Danish registries, 2003–2017. LQTS patients were matched 1:5 with controls on sex and age.ResultsWe matched 463 LQTS patients with 2315 controls from the background population. Mean age was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…The transition from increased glucose-stimulated insulin secretion to subsequent hyposecretion possibly results from hypersecretion-induced islet dysfunction. This may explain the association to both post-prandial hypoglycemia in LQTS patients with LoF variants 11 , as well as increased risk of T2D-associated with KCNQ1 variants 6 , 21 , 22 and the higher prevalence of diabetes in LQTS patients 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition from increased glucose-stimulated insulin secretion to subsequent hyposecretion possibly results from hypersecretion-induced islet dysfunction. This may explain the association to both post-prandial hypoglycemia in LQTS patients with LoF variants 11 , as well as increased risk of T2D-associated with KCNQ1 variants 6 , 21 , 22 and the higher prevalence of diabetes in LQTS patients 23 .…”
Section: Discussionmentioning
confidence: 99%
“…A study in human pancreatic beta-cells showed that some of these susceptibility variants near KNCQ1 were accompanied by either reduced depolarization-induced insulin secretion or impaired insulin granule docking 22 . It is unknown whether these variants influence K v 7.1 channel function; however, a recent Danish retrospective cohort study showed that LQTS patients have a higher prevalence of diabetes, suggesting reduced K + currents could be involved 23 . Moreover, in mice, a mutation in the noncoding region of the Kcnq1 locus on the paternal allele was shown to reduce pancreatic beta-cell mass through epigenetic modification of cell cycle inhibitor cyclin-dependent kinase inhibitor 1C ( Cdkn1c ) 24 .…”
Section: Introductionmentioning
confidence: 99%
“…One of these reasons could be lifestyle. Individuals with LQTS have a higher burden of psychiatric comorbodities compared to the background population, which may represent an increased burden of depression and anxiety, potentially related to living with a cardiac diagnosis 6 . This may severely impact their lifestyle, including activity levels and dietary choices.…”
Section: Knowledge Gaps and Future Areas Of Interestmentioning
confidence: 99%
“…Interestingly, patients with LQTS also show a higher burden of diabetes compared to the background population, 6 seemingly paradoxical given the post‐prandial hyperinsulinaemia. Furthermore, in a large number of genome‐wide association studies (GWAS), KCNQ1 has been consistently identified as a type 2 diabetes susceptibility locus 7‐9 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the first description by Jervell and Lange–Nielsen of a familial condition associated with congenital deafness, prolonged QT intervals and sudden death in 1957, 1 LQTS has been the most investigated cardiac channelopathy. LQTS has been described worldwide in many ethnic groups, with significant burden of arrhythmogenic and psychological consequences 2,3 . Many in‐depth reviews have been written outlining the genetic and molecular basis of LQTS; however, the present review seeks to offer the general cardiologist an overview of LQTS pathophysiology, diagnosis, risk stratification and management.…”
Section: Introductionmentioning
confidence: 99%